Cysteine thiol-to-sulfonate oxidation induces unfolding for the functional switching of the extracellular HMGB1 protein - Jonathan M. Paz-Villatoro; Binhan Yu; Orion Songe; Xi Wang; Junji Iwahara (Proceedings of the National Academy of Sciences, 2026)
Oxidation of cysteine thiols to sulfonate groups (–SO 3 – ) by reactive oxygen species can regulate protein function. Near the end of inflammation, this modification in the extracellular HMGB1 protein abolishes its proinflammatory activity. Using NMR spectroscopy, we investigated how thiol-to-sulfonate oxidation switches HMGB1’s function. Our data show that the oxidation of cysteine 106 (C106) induces unfolding of the HMGB1 B-box domain. In contrast, other chemical modifications, such as S-glutathionylation, at the same cysteine did not have this effect, highlighting the unique impact of thiol-to-sulfonate oxidation. Employing 13 C direct-detected NMR, we characterized the oxidized B-box domain. NMR data confirmed global unfolding but revealed residual α-helical propensity near the second and third helices. NMR paramagnetic relaxation enhancement data revealed electrostatic impacts of the C106 thiol-to-sulfonate oxidation. To test whether unfolding is driven by negative charge in a hydrophobic environment, we analyzed the C106D variant, as aspartate electrostatically mimics cysteine sulfonate. However, the C106D variant remained folded, even though NMR confirmed a negative charge at D106. Further NMR experiments showed that the –SO 3 − group at residue 106 drastically slows down the protein folding kinetics, compared with the –COO − group at the same position, suggesting that –SO 3 − introduces a large desolvation penalty for protein folding. This study illuminates protein unfolding via thiol-to-sulfonate oxidation of a cysteine residue in a hydrophobic environment as a mechanism for protein functional switching. Since HMGB1 is a therapeutic target for inflammatory diseases, understanding this inactivation mechanism offers insight for designing covalent inhibitors.